Inverted silicon nanocones for a next generation of silicon-based optoelectronics - Schmitt, Sebastian W.; Sarau, George; Göbelt, Manuela; Christiansen, Silke (Optics InfoBase Conference Papers, 2014)
The study introduces a novel type of photonic structure, the inverted silicon nanocone (SiNC). It exhibits a unique photonic mode formation, and permits the design of novel Si-based optoelectronic devices such as solar cells LEDs or optical sensors.
CRIS-Team Scopus Importer:2023-03-07